Find the value of x it's simple easy
![](https://hi-static.z-dn.net/files/da4/7bdacfe7594bc48af5303180cf917a54.jpg)
Answers
Step-by-step explanation:
Given :-
(-2/3)^-13 × (3/-2)^8 = (-2/3)^(-2x+1)
To find :-
Find the value of x ?
Solution :-
Given equation is
(-2/3)^-13 × (3/-2)^8 = (-2/3)^(-2x+1)
We know that a^-n = 1/a^n
(-2/3)^-13 = 1/(-2/3)^13 = (-3/2)^13
Above equation becomes
=> (-3/2)^13 × (-3/2)^8 = (-2/3)^(-2x+1)
=> (-3/2)^(13+8) = (-2/3)^(-2x+1)
Since a^m × a^n = a^(m+n)
=> (-3/2)^21 = (-2/3)^(-2x+1)
=> (-2/3)^-21 = (-2/3)^(-2x+1)
Since a^-n = 1/a^n
=> -21 = -2x+1
Since the bases are equal then exponents must be equal.
=> -2x+1 = -21
=> -2x = -21-1
=> -2x = -22
=> x = -22/-2
=> x = 11
Therefore, x = 11
Answer:-
The value of x for the given problem is 11
Check:-
LHS of the given equation is
(-2/3)^-13 × (3/-2)^8
=> (-2/3)^-13 × (-2/3)^-8
Since a^-n = 1/a^n
=> (-2/3)^(-13-8)
=> (-2/3)^-21----------(1)
If x = 11 then RHS of the given equation is
(-2/3)^(-2×11+1)
=> (-2/3)^(-22+1)
=> (-2/3)^-21-----------(2)
From (1)&(2)
LHS = RHS is true for x = 11
Verified the given relations in the given problem.
Used formulae:-
- a^-n = 1/a^n
- a^m × a^n = a^(m+n)
- If the bases are equal then exponents must be equal.